Viburnum is a symbol of Ukraine and a source of biologically active substances - Stavychna, Antonina; Kaminska (Halapsina), Svitlana (My University, 2023)
The presence of phytoncides as medicinal raw materials use the fruits, bark, flowers and roots of viburnum. Fruit juice is used to treat peptic ulcer disease, edema, normalize the acidity of gastric juice, and provide prevention of oncology of the breast and stomach.
Keywords: viburnum; vitamins; fruits; freezing; food industry; кафедра технології оздоровчих продуктів